日系アメリカ文学の変容とヒサエ・ヤマモト - 平石（稲木）, 妙子; ヒライシ イナギ, タエコ; Inagi-Hiraishi, Taeko (2019)
Hisaye Yamamotoʼs works have been widely read particularly since the publication of Seventeen Syllables and Other Stories, a collection of her works in 1988. Most of the reviews and studies about her have mainly focused on the significance of gender, Japanese American culture and hybrid identity. However, it should be noted that many recent studies on Yamamoto have shifted to an analysis of an interracial solidarity in her works. One such work is “The Eskimo Connection.” Although it has not been fully examined by scholars, a reading of“ The Eskimo Connection” will surely lead us to recognize that Yamamoto had a sharp insight into the possibilities and limits of interracial and interethnic relationships among US minorities. The aim of this paper is to point out the significance of“ The Eskimo Connection” by comparing it with Cynthia Kadohataʼs Weedflower and to examine Yamamotoʼs influence on such a postmodern writer as Kadohata. “The Eskimo Connection” and Weedflower are similar in that they deal with relationships between Japanese Americans and Native Americans. “The Eskimo Connection” （1983） is a fictional narrative about correspondence between a young incarcerated Native American man, Alden, and an older Japanese American woman, Emiko. Although Emiko is, at first, hesitant to respond to Alden when he asks her to give him some comments on an essay he has written, she finally decides to answer his request, and starts a two-year correspondence with him. Emiko begins to understand his inner sufferings and to sympathize with him because his situation reminds her of her internment experience during World War II. Kadohataʼs Weedflower （2006） is set at Poston internment camp during World War II. Sumiko, a 12-year-old Nisei girl, happens to meet Frank, a Mohave boy, at the camp. At first they both feel anger toward each other, until Sumiko learns from Frank that Native Americans have been denied civil rights like Japanese Americans. Subsequently they begin to feel empathy with each other when they come to know that ...